DEACTUALIZATION OF HIGHER EDUCATION ON THE EXAMPLE OF STUDYING FOREIGN LANGUAGES - Nalyvaiko, Oleksii; Kalistova, Olena; Poliakov, Danylo (Educological discourse, 2021)
The article analyzes the main reasons for de-actualization of higher education in Ukraine on the example of teaching foreign languages. The authors identified four main reasons for the deactualization of higher education: a difficult socio-economic situation caused by an incompetent organization of the production forces of the Ukrainian economy, low quality of educational services, depopulation of the Ukrainian population and a decrease in the quality of the teaching staff, a permanent increase in the cost of higher education. To confirm our assumptions, we carried out an introduction of students from different parts of Ukraine who study a foreign language. We interviewed six respondents from different universities across Ukraine about the topic: V.N. Karazin Kharkiv National University, Horlivka Institute for Foreign Languages, Ivan Franko National University of Lviv, Kyiv National Linguistic University, National Technical University “Kharkiv Polytechnic Institute” and Ternopil Volodymyr Hnatiuk National Pedagogical University. Every respondent was given a name (A-F) in order to keep their anonymity. We have presented the results of the interview. Students say that problems do not always depend on universities, but personal traits of students and teachers and modern tendencies in labor market. We gave some recommendations: the curriculum must be corrected in favor of main subjects or even subjects that will make graduates more appropriate for some posts than people without degree; teaching staff must have special pedagogical degree in order to improve their pedagogical skills; universities need to employ native speakers of taught languages; universities need to elaborate such study programs that will make their graduates more attractive candidates in labor market. The main conclusion must be so: the system of higher education has to keep up with the times and change itself according to labor market, students’ beliefs and modern tendencies in science and technology.